The Semiotics of Luck: Interpreting Visual Metaphors in the Animated Film - Cahyani, Putri; Hasbi, Muhammad (Universitas Sulawesi Barat, 2024)
This study examines the symbolic meanings conveyed through visual metaphors in the 2022 animated film Luck. Utilizing Charles Sanders Peirce's semiotic theory, the research aims to identify and interpret the signs present within the movie. The study employs a qualitative research paradigm and a descriptive approach, collecting data through repeated viewings of the film and cataloging the identified signs as icons, indexes, or symbols per Peirce's triadic model. The analysis reveals a total of 16 signs, comprising 3 icons, 4 indexes, and 9 symbols, which are then subjected to semiotic analysis. The findings demonstrate that the iconic signs, such as the photograph of the protagonist Sam as a child, symbolize his past. Indexical signs, like the list of orphanages he resided in, indicate his nomadic upbringing. Symbolic representations, including the four-leaf clover and the leprechaun characters, signify cultural notions of luck and fortune. The pervasive use of the color green and imagery like ladybugs further reinforce the thematic exploration of luck and prosperity. Overall, the movie Luck employs a rich tapestry of visual symbols to delve into complex concepts like fate, perspective, and fortune, enhancing the narrative depth and enriching the viewing experience.